RECONSTRUCTION OF THE ORAL TRADITIONS OF ONANG-ONANG CULTURE THROUGH CULTURAL LITERACY TO IMPROVE THE COMMUNITY LITERACY DEVELOPMENT INDEX - Dedi Zulkarnain Pulungan; Hamni Damayanti (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to analyse the reconstruction of the Onang-Onang oral tradition based on cultural literacy as an effort to improve the Community Literacy Development Index (IPLM). Onang-Onang is an oral tradition of the Mandailing people that embodies aesthetic, moral, religious and social values, and serves as a medium for the intergenerational transmission of cultural values. However, the passage of time, modernisation, and the declining interest of the younger generation in local traditions have posed challenges to the continuity of Onang-Onang. This study employs a literature review method with a descriptive-analytical approach through the examination of various relevant academic sources. The findings indicate that the reconstruction of Onang-Onang can be achieved through documentation, digitisation, reinterpretation of meaning, and integration into education and community literacy activities. These strategies not only ensure the continuity of the tradition but also broaden public access to local cultural knowledge. Thus, the reconstruction of Onang-Onang art based on cultural literacy has the potential to be an effective step in strengthening cultural identity whilst supporting the contextual and sustainable improvement of the Community Literacy Development Index (IPLM).